2007
DOI: 10.9793/elsj1984.24.33
|View full text |Cite
|
Sign up to set email alerts
|

C-to-v Incorporation and Subject Raising Across Cp-Boundary

Abstract: The Subject Raising (SR) in Japanese is an A-movement across a CPboundary. It remains unclear why such a movement is possible without violating the Phase Impenetrability Condition. To answer this question, it is proposed in this article that the head of the embedded CP in the SR construction undergoes incorporation to the selecting V. It is argued that this proposal not only solves the above mentioned problem but also account for (i) the otherwise systematic locality effects on A-movement in Japanese, (ii) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…2 A breakthrough in RTO research in the minimalist era can be found in Sakai (1998), which argues that Indeterminate Pronoun Binding helps make it clear that the raised DP is originally located within the embedded CP. Hiraiwa (2005) and Ogawa (2007) also present very intriguing explanations for the data contained in Sakai (1998).…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…2 A breakthrough in RTO research in the minimalist era can be found in Sakai (1998), which argues that Indeterminate Pronoun Binding helps make it clear that the raised DP is originally located within the embedded CP. Hiraiwa (2005) and Ogawa (2007) also present very intriguing explanations for the data contained in Sakai (1998).…”
Section: Introductionmentioning
confidence: 92%
“…That is, indeterminate pronouns can be licensed by reconstruction. On the other hand, the latter including Kishimoto (2001), Hiraiwa (2005), and Ogawa (2007) claim that indeterminate pronouns not be licensed outside the domain of mo. Though more research is needed, I will take the position of a strict version of the freezing effect in this paper, based on my own judgment.…”
Section: The Rto-ipb Paradoxmentioning
confidence: 99%
See 3 more Smart Citations